Epigenetic Modifications in Tumor-Associated Macrophages: A New Perspective for an Old Foe - Niu, Yuqin; Chen, Jianxiang; Qiao, Yiting (Frontiers in Immunology, 2022)
Tumorigenesis is frequently accompanied by chronic inflammation, and the tumor microenvironment (TME) can be considered an ecosystem that consists of tumor cells, endotheliocytes, fibroblasts, immune cells and acellular components such as extracellular matrix. For tumor cells, their survival advantages are dependent on both genetic and epigenetic alterations, while other cells mainly present epigenetic modifications. Macrophages are the most plastic type of immune cells and undergo diverse epigenetic alterations in the TME. Some of these epigenetic modifications mitigate against cancer progression, and others accelerate this process. Due to the complex roles of macrophages in the TME, it is urgent to understand their epigenetic modifications associated with the TME. Here, we mainly summarize recent findings on TME-associated epigenetic alterations of tumor-associated macrophages (TAMs), including DNA methylation, posttranslational modifications of histone proteins, chromatin remodeling, and noncoding RNA-mediated epigenetic regulation. At the end of this review, we also discuss the translational potential of these epigenetic modifications for developing novel cancer therapies targeting TAMs.